A Questão regional e a formação do discurso desenvolvimentista na Amazônia - FERNANDES, Danilo Araújo (Universidade Federal do Pará, 2012)
This thesis is a study of the historical formation of regional discourse on the issue Amazon and its relation to the national-developmentalist period in Brazil. In its first part, the study presents the goals and theoretical-methodological work, based on the method of Michel Foucault archeogenealogical and the theory of ideology of Paul Ricoeur. Then the study presents the historical basis of conceptual and ideological training of the cycle of developmentalism in Brazil, as well as the theoretical discourse and the regional question in Brazil. In this part, what is evident is the importance of the correlation and interdependence between the regional issue and the formation of national discourse of development in Brazil and in that sense, the work of Celso Furtado stands out as an important element of development discourse that will represent interpretation of a regional issue as constituting a larger project of national development. At the end of the paper, we highlight the connection between the institutional environment of national-development and the formation of a Brazilian tradition of regionalist thinking that Amazon will have great influence in the 40 and 50, and will be responsible for preparing a development discourse regionalist from the influence of authors such as Euclides da Cunha and Gilberto Freyre. Authors such as Arthur Cezar Ferreira Reis, Leandro Tocantins and Djalma Batista, among others, are considered some of the most responsible for drafting an intellectual discourse that, according to one of the main conclusions of the study, has its conditions of possibility created and driven from the reality political-institutional context that is the formation of developmental institutions in the Amazon in the 40 and 50. Forming a discursive formation which will assign the name of developmentalism-regionalist.